Standards of Fluid Biomarker Collection and Pre-analytical Processes in Humans and Mice: Recommendations by the Ataxia Global Initiative Working Group on Biomarkers - Filippo M. Santorelli; Hayley S. McLoughlin; Justin M. Wolter; Daniele Galatolo; Matthis Synofzik; David Mengel; Puneet Opal; Antonijevic Irina; Auburger Georg; Bataller Luis; Bertini Enrico; Boesch Sylvia; et al. (The Cerebellum, 2023)

Standards of NGS Data Sharing and Analysis in Ataxias: Recommendations by the NGS Working Group of the Ataxia Global Initiative - Danique Beijer; Brent L. Fogel; Sergi Beltran; Matt C. Danzi; Andrea H. Németh; Stephan Züchner; Matthis Synofzik; Astrid Adarmes; Saud Alhusaini; Mahmoud Reza Ashrafi; Luis Bataller; Enrico Bertini; et al. (The Cerebellum, 2023)
The Ataxia Global Initiative (AGI) is a worldwide multi-stakeholder research platform to systematically enhance trial-readiness in degenerative ataxias. The next-generation sequencing (NGS) working group of the AGI aims to improve methods, platforms, and international standards for ataxia NGS analysis and data sharing, ultimately allowing to increase the number of genetically ataxia patients amenable for natural history and treatment trials. Despite extensive implementation of NGS for ataxia patients in clinical and research settings, the diagnostic gap remains sizeable, as approximately 50% of patients with hereditary ataxia remain genetically undiagnosed. One current shortcoming is the fragmentation of patients and NGS datasets on different analysis platforms and databases around the world. The AGI NGS working group in collaboration with the AGI associated research platforms—CAGC, GENESIS, and RD-Connect GPAP—provides clinicians and scientists access to user-friendly and adaptable interfaces to analyze genome-scale patient data. These platforms also foster collaboration within the ataxia community. These efforts and tools have led to the diagnosis of > 500 ataxia patients and the discovery of > 30 novel ataxia genes. Here, the AGI NGS working group presents their consensus recommendations for NGS data sharing initiatives in the ataxia field, focusing on harmonized NGS variant analysis and standardized clinical and metadata collection, combined with collaborative data and analysis tool sharing across platforms.

Laquinimod Treatment Improves Myelination Deficits at the Transcriptional and Ultrastructural Levels in the YAC128 Mouse Model of Huntington Disease - Marta Garcia-Miralles; Nur Amirah Binte Mohammad Yusof; Jing Ying Tan; Carola I. Radulescu; Harwin Sidik; Liang Juin Tan; Haim Belinson; Neta Zach; Michael R. Hayden; Mahmoud A. Pouladi (Molecular Neurobiology, 2019)